Wiktora Woroszylskiego spotkania z Rosją - Pawletko, Beata (Przegląd Rusycystyczny, 2012)
Beata Pawletko Uniwersytet Śląsk, Katowice, Poland bpawletko@wp.pl ВИКТОРА ВОРОШИЛЬСКОГО ВСТРЕЧТИ С РОССИЕЙ Резюме Цель данной работы это рассмотрение богатых личных связей Виктора Ворошиль-ского с Россией и россиянами, его борьбы со стереотипами, влияющими часто на отрицательное отношение поляков к России, что показали обсуждаемые в статье инициативы, в которых Ворошильский принимал активное участие. В поле зрения автора данной статьи находятся не только тексты, посвященные русским темам, но прежде всего исследовательские работы Ворошильского, касающиеся творчества русских писателей, а также его многие превосходные переводы. WIKTOR WOROSZYLSKI`S MEETINGS WITH RUSSIA Summary The main aim of this paper is to present rich personal relations of Wiktor Woroszylski with Russia and Russians, his fight against stereotypes, which often influenced negatively on reception of Russia in Poland, what was showed by discussed in the paper initiatives in which Woroszylski was involved passionately. The author of this article is interested not only in the texts devoted to Russian matters but, first of all, in Woroszylski`s researches concerning the oeuvre of Russian writers as well as his impressive translational achievements.